2007
DOI: 10.2307/25065857
|View full text |Cite
|
Sign up to set email alerts
|

A phylogeny and new classification for Mesembryanthemoideae (Aizoaceae)

Abstract: We present a phylogeny for Mesembryanthemoideae (Aizoaceae) based on sampling of nearly all species and subspecies of the subfamily and analysis of cptrnL-F, rbcL-atpB, rps16, nrITS1 and morphology. The larger genera Phyllobolus and Mesembryanthemum are not monophyletic. Although some clades can be circumscribed with morphological (often homoplasious) synapomorphies, several clades are impossible to characterise morphologically. We recognise a single genus, Mesembryanthemum, in Mesembryanthemoideae. The genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 21 publications
0
57
1
1
Order By: Relevance
“…Ollerton et al 2007), since in this case, floral rewards seem especially difficult to gather by insects other than flies with a cushion-like labium. In terms of its pollination system, A. sylvestris is regarded a supergeneralist (Olesen et al 2007), since its protandrous flowers are visited by a wide range of insects representing several taxonomic orders (Ellis and Ellis-Adam 1993;Zych et al 2007;Niemirski and Zych 2011). It has open, dish-shaped flowers with no additional morphological adaptations that would restrict the access of insect visitors to floral rewards.…”
Section: Discussionmentioning
confidence: 99%
“…Ollerton et al 2007), since in this case, floral rewards seem especially difficult to gather by insects other than flies with a cushion-like labium. In terms of its pollination system, A. sylvestris is regarded a supergeneralist (Olesen et al 2007), since its protandrous flowers are visited by a wide range of insects representing several taxonomic orders (Ellis and Ellis-Adam 1993;Zych et al 2007;Niemirski and Zych 2011). It has open, dish-shaped flowers with no additional morphological adaptations that would restrict the access of insect visitors to floral rewards.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation transect in Kabaty was a small fragment of a larger area of similar character, and insects (mostly opportunistic flies) could unrestrictedly search for other plants or floral patches, whereas Ochota transect was surrounded by an otherwise hostile environment, and pollinators (mostly bees that usually show floral constancy) could only forage within the actual site which largely restricted their choice. In both study sites, the most connected plants belonged to families Fabaceae and Apiaceae and these are known to be visited by a vast range of floral visitors (Ellis and Ellis-Adam 1993;Proctor et al 1996;Willmer 2011), the former being especially attractive to bees because of its protein-rich pollen (Goulson et al 2005;Hanley et al 2008; for contrasting opinion see, however, Roulston et al 2000), whereas the latter are typical phenotypical generalists with open, easily accessible flowers (Olesen et al 2007b;Ollerton et al 2007) and are known to be visited by a taxonomically diverse array of generalist insects, especially flies (see e.g., Zych 2004;Zych et al 2007). Also, the insect species recorded in our study Urban pollination networks 509 networks were largely generalists.…”
Section: Discussionmentioning
confidence: 99%
“…Although umbellifers are generally regarded as generalists in terms of their floral visitors (Corbet 2006;Olesen et al 2007;Ollerton et al 2007), fly-pollination [myophily, as described in Willmer (2011), p. 308], is probably typical of Apiaceae (Proctor et al 1996;Zych 2004) and, to date, has been reported for many other European members of this family (Grace and Nelson 1981;Zych 2002Zych , 2007Niemirski and Zych 2011), including O. palustre. Diptera are also important pollinators of umbellifers on remote islands (Pérez-Bañón et al 2007), and on other continents (e.g.…”
Section: Pollination Importancementioning
confidence: 99%